Charles Abbot Ricketts, Ed Ricketts father. - unknown:::Creator::::::::::::
Charles Abbott Ricketts, Ed Rickett's father, in a lab smock, in front of first Pacific Biological Laboratory. Abbott worked in Ed's lab until he died in 1936.